Corporate Social Responsibility pada PT Unggul Widya Teknologi Lestari Kabupaten Mamuju Utara - Ike Dwiyanti (Departemen Ilmu Pemerintahan Fisip Unhas, 2018)
This study aims to find out the Implementation of Regional Social Responsibility (CSR) Regulations on PT Unggul Widya Teknologi Lestari Lestari in North Mamuju region, and the factors that influence it. To achieve these objectives, used qualitative research methods by parsing data descriptively. Data collection technique is done by observation, interview, and document and archive by using qualitative descriptive analysis technique. Based on the results of research, in the implementation there are various factors that influence the supporting factors and inhibiting factors. Factors supporting the existence of the Law that regulates, and Human resources are available. And the inhibiting factors are poor government and corporate relationships, public understanding of corporate social responsibility or lack of CSR, and government efforts in dealing with CSR issues.